Observation of the pulse oximeter trace to estimate systolic blood pressure during spinal anaesthesia for Caesarean section: the effect of body mass index. (4th July 2017) - Samuel, T; van Dyk, D; Lombard, CJ; Dyer, RA
Abstract : Background: The estimation of systolic blood pressure by disappearance and reappearance of the pulse oximeter trace during cuff inflation and deflation was compared with non-invasive blood pressure (NIBP) measurement, across the range of body mass index (BMI), during spinal anaesthesia for Caesarean section. Methods: Seventy-five parturients were recruited, with BMI of < 30 (Group 1), 30–40 (Group 2), and > 40 kg/m 2 ((morbidly obese, Group 3). A non-invasive blood pressure monitor was used with the pulse oximeter probe on the ipsilateral arm. Estimations were done before induction and 5 min after induction of spinal anaesthesia, during cuff inflation and deflation. Bland and Altman analysis was performed and the concordance correlation coefficient (r) estimated. Results: For estimation of systolic blood pressure during cuff inflation under spinal anaesthesia in Groups 1, 2 and 3: r = 0.57, 0.74 and 0.91; bias = –0.4, –2.9 and 0.8 mmHg, and limits of agreement = –27.7 to 26.9, –27.7 to 21.9, and –15.9 to 17.5 mmHg respectively. The mean (SD) time saved by estimation during inflation compared with measurement in Groups 1, 2 and 3 was 22.8 (13.2) s, 30.0 (11.6) s and 33.0 (15.6) s respectively. In Group 3, the percentage error was ± 13% of mean systolic blood pressure. Conclusions: Estimation of systolic blood pressure during cuff inflation under spinal anaesthesia in the morbidly obese is more precise than in lower BMI parturients. Time to estimation is relevantly shorter than measurement. This could improve patient safety by rapid and accurate identification of hypotension in these high-risk patients. This estimation method is associated with limits of agreement that may be clinically significant even in morbidly obese patients, and should not be considered a replacement for subsequent NIBP measurement.